PEMANFAATAN TEPUNG AZOLLA PADA PAKAN UNTUK MENINGKATKAN PERTUMBUHAN BENIH NILA GIFT (Oreochromis sp.) - Achmad Mushocheh; Febriyanti, Titin; M. Hadziq Qulubi (JURNAL LEMURU, 2023)
The purpose of this study was to determine the effect of azolla flour to growth of GIFT tilapia (Oreochromis sp.). Sources of animal protein that can be used people's nutrition like fish. Many people create business by cultivating fish such as GIFT tilapia. Fish farming business is strongly influenced by the availability of adequate feed in quantity and quality to support optimal results. However, cultivators face problems with production costs, especially feed which is quite high, so they must look for alternatives to reduce production costs, one of which is by adding sources of raw materials in the form of using Azolla. The research method used experimental using a completely randomized design with 4 treatments and 4 replications. The treatments tested were P0 (without azolla flour (control)); P1 (25% azolla flour); P2 (Azolla flour 50%); P3 (75% azole flour). The research variables observed were absolute growth, specific growth, survival, and feed conversion. The results showed that the treatment was significantly different in absolute growth, located in the P3 treatment having the lowest weight of 4.05 g. For other variables, the differences are not significant. Specific growth ranged from 1.64–1.81% day, survival ranged from 80–90%, and feed conversion ranged from 1.63 - 1.75%.